Elasticity of axial nanowire heterostructures with sharp and diffuse interfaces. (February 2020) - Romanov, A.E.; Kolesnikova, A.L.; Gutkin, M.Yu.; Dubrovskii, V.G.
Abstract: We present a theoretical analysis of the elastic properties of lattice-mismatching axial nanowire heterostructures. In contrast to the previous works, we take into account non-ideal diffuse interfaces between the dissimilar materials, which are often observed in nanowire heterostructures. Another important result is the existence of a maximum of the elastic energy in a double nanowire heterostructure as a function of its height. The obtained results are applicable to a wide range of material combinations and can be used for understanding and controlling the crystal quality and physical properties of nanowire-based heterostructures for different applications. Graphical abstract: Image, graphical abstract